2015
DOI: 10.1093/eurheartj/ehv321
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA-221/-222 cluster balances the antiviral and inflammatory response in viral myocarditis

Abstract: The miR-221/-222 cluster orchestrates the antiviral and inflammatory immune response to viral infection of the heart. Its inhibition increases viral load, inflammation, and overall cardiac injury upon VM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 39 publications
0
56
0
Order By: Relevance
“…The same miRNA was confirmed to play a major role in viral myocarditis, when miR-155 levels in mouse cardiac tissue were identified to increase during carditis in a macrophage dependent manner [130]. Another recent study found miR-221 and miR-222 as key regulators of the cardiac response to viral myocarditis [131]. This study was performed in cardiac tissue samples of myocarditis patients, as well.…”
Section: Infective Carditismentioning
confidence: 65%
“…The same miRNA was confirmed to play a major role in viral myocarditis, when miR-155 levels in mouse cardiac tissue were identified to increase during carditis in a macrophage dependent manner [130]. Another recent study found miR-221 and miR-222 as key regulators of the cardiac response to viral myocarditis [131]. This study was performed in cardiac tissue samples of myocarditis patients, as well.…”
Section: Infective Carditismentioning
confidence: 65%
“…Inhibition of miR-211/miR-222 augments viral load and strongly aggravates CVB3-induced cardiac injury, whereas a high level of these 2 miRNAs reduces viral replication. 155 In brief, accumulated evidence indicates that CVB3-induced differential expression of miRNAs plays a crucial role in modulating host and viral gene expression, and in turn directly or indirectly promotes CVB3 pathogenesis.…”
Section: Virus-induced Direct Damagementioning
confidence: 99%
“…The miRNA cluster from chr19 (miR‐512‐1/516a‐2) may be useful in the treatment of autoimmune diseases such as rheumatoid arthritis and Sjogren's syndrome (Bullerdiek & Flor, ). miR‐221/222 cluster regulates antiviral and inflammatory responses to viral infection of the heart (Corsten et al, ). miR‐212/132 cluster has shown to be altered in Alzheimer's disease (Pichler et al, ).…”
Section: Mirna Clusters and Other Diseasesmentioning
confidence: 99%